Iodine dynamics in the terrestrial environment - Bowley, Hannah E. (2013)
The aim of this work was to investigate the effect of soil properties on soil iodine dynamics and uptake to plants. Soil and vegetation samples were collected from across eastern Northern Ireland (NI) to form the basis of most experimental work; samples from the Rothamsted Park Grass archive were used to investigate the role of changing soil chemistry through time and due to selected fertiliser applications; and iodine dynamics in humic acid (HA) were studied to improve understanding of the role of organic matter in soils. Input of iodine in rainfall was considered in the context of samples from both locations, and the additional influences of coastal proximity, soil type and underlying geology were reviewed for the NI samples. Total iodine analysis was carried out using extraction with TMAH and quantification by ICP-MS; aqueous iodine speciation was determined using HPLC and SEC coupled with ICP-MS.